Comparison of the Working Memory Load in N-Back and Working Memory Span Tasks by Means of EEG Frequency Band Power and P300 Amplitude - Scharinger, Christian; Soutschek, Alexander; Schubert, Torsten; Gerjets, Peter (Frontiers in Human Neuroscience, 2017)
According to theoretical accounts, both, N-back and complex span tasks mainly require working memory (WM) processing. In contrast, simple span tasks conceptually mainly require WM storage. Thus, conceptually, an N-back task and a complex span task share more commonalities as compared to a simple span task. In the current study we compared an N-back task, a complex operation span task (Ospan), and a simple digit span task (Dspan) by means of typical WM load-related measures of the Electroencephalogram (EEG) like the parietal alpha and beta frequency band power, the frontal theta frequency band power, and the P300 amplitude, to examine whether these tasks would show commonalities or differences in WM processing-load. We expected that increasing WM-load would generally lead to a decreased alpha and beta frequency band power, an increased theta frequency band power, and a decreased P300 amplitude. Yet, based on the conceptual considerations, we hypothesized that the outcomes of these measures would be more comparable between the N-back and the Ospan as compared to the Dspan. Our hypotheses were partly confirmed. The N-back and the Ospan showed timely more prolonged alpha frequency band power effects as compared to the Dspan. This might indicate higher demands on WM processing in the former two tasks. The theta frequency band power and the P300 amplitude were most pronounced in the N-back task as compared to both span tasks. This might indicate specific demands on cognitive control in the N-back task. Additionally, we observed that behavioral performance measures correlated with changes in EEG alpha power of the N-back and the Ospan, yet not of the Dspan. Taken together, the hypothesized conceptual commonalities between the N-back task and the Ospan (and, for the Dspan, differences) were only partly confirmed by the electrophysiological WM load-related measures, indicating a potential need for reconsidering the theoretical accounts on WM tasks and the value of a closer link to electrophysiological research herein.